Using artificial intelligence methods to assess academic achievement in public high schools of a European Union country - Cruz-Jesus, Frederico (2020)
Cruz-Jesus, F., Castelli, M., Oliveira, T., Mendes, R., Nunes, C., Sa-Velho, M., & Rosa-Louro, A. (2020). Using artificial intelligence methods to assess academic achievement in public high schools of a European Union country. Heliyon, 6(6), [e04081]. https://doi.org/10.1016/j.heliyon.2020.e04081